2016
DOI: 10.21037/atm.2016.12.52
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of curcumin on Helicobacter pylori infection

Abstract: Background: Curcumin is a well-established natural molecule with significant biological and pharmaceutical effects. Its effects on Helicobacter pylori (H. pylori) infection have been repeatedly confirmed both in animal and human models. This study directly compared five different samples to evaluate if the effects are general or if they differ among samples.Methods: Using a mouse model, we studied the effects of curcumin on lipid peroxide (LPO) level, myeloperoxidase (MPO) and urease activity, number of coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Currently, different control strategies were examined to inhibit the biofilm formation to lower the recurrent H. pylori infections [39,40]. In the present investigation, we have showed that H. pylori can be controlled effectively by exposure to AiiA‐AgNPs.…”
Section: Discussionmentioning
confidence: 62%
“…Currently, different control strategies were examined to inhibit the biofilm formation to lower the recurrent H. pylori infections [39,40]. In the present investigation, we have showed that H. pylori can be controlled effectively by exposure to AiiA‐AgNPs.…”
Section: Discussionmentioning
confidence: 62%
“…To the best of our knowledge, the specific antimicrobial mechanism of curcumin against Campylobacter has not been investigated. The effect of curcumin against Helicobacter pylori, a highly relevant bacterium to Campylobacter, has been repeatedly confirmed in several studies (Di Mario et al, 2007;Zaidi et al, 2009;Sarkar et al, 2016;Vetvicka et al, 2016). One study of using a high-throughput screening of 5,000 chemical compounds discovered that the inhibition of H. pylori by curcumin was due to the inhibition of shikimate pathway (Han et al, 2006).…”
Section: Plant-based Antimicrobialsmentioning
confidence: 89%
“…Both pro-inflammatory NF-κB and the motogenic response in H. pylori -infected epithelial cells were inhibited by curcumin [60]. In recent trials, the addition of curcumin to triple therapy regimes ameliorated the oxidative stress and histopathologic changes in chronic gastritis-associated H. pylori infections [61,62,63]. All together, these studies suggest that curcumin can be a useful supplement to improve the gastric mucosal protection against chronic inflammation and may prevent the carcinogenic changes in patients with chronic gastritis associated with H. pylori (Figure 2).…”
Section: Efficacy Of Curcumin To Treat the Impairment The Gastric mentioning
confidence: 99%